Natural disasters and remittances: Exploring the linkages between poverty, gender and disaster vulnerability in Caribbean SIDS - Marlene Attzs (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper explores the linkages between poverty and disaster vulnerability in the context of remittance flows to households in the Caribbean. Jamaica is used as the case study country. The paper discusses the channels through which natural disasters and remittances affect each other but also reviews the distribution of female-headed households in Jamaica as a percentage of households living below the poverty line and seeks to identify whether flows of remittances alleviate the post-disaster living conditions of such households. The dislocation of households coupled with the loss of livelihoods caused by natural disaster, which usually affects the poor disproportionately, provides a push factor for
Keywords: Q54; F24; J16; 330; natural disasters; remittances; economics of gender; Jamaica; Naturkatastrophe; Geschlecht; Rücküberweisung (Migranten); Insel; Karibische Staaten; Jamaika